(untitled) (AYUSHDHARA, 2018)
Lipodermatosclerosis (Sclerosing Panniculitis) is uncommon and is associated with venous or arterial insufficiency. It presents as tender, indurated plaques in the lower legs. Lipomembranous panniculitis is a form of fat necrosis associated not only with stasis but also with autoimmune diseases, peripheral vascular diseases, and infection. There is fat necrosis, sclerosis, and a lymphocytic infiltrate in a lobular pattern. It appears to be a consequence of ischemia and venous stasis. It most frequently occurs in women and are usually accompanied by signs of venous insufficiency It primarily treated with compression therapy to improve venous insufficiency. Venous insufficiency is also managed by leg elevation; regular exercise; not sitting or standing in one place for long period of time; and weight loss if overweight. A 65 years old male patient was having complaints of swelling over bilateral leg, wound over rt. leg since 8 month. Total 19 sittings of Jalauka Avacharan are done on alternate day. Guduchi Churna, Londra Churna, Haridra Churna, Daruharidra Churna, Kusta Churna, Bakuchi Churna all 100 gm each are mixed and divided into 120 parts. 5 gm of this mixture is given in BD dose for 60 days. Cleaning and dressing of wound done every day with Vranshodhan tail.